Mengkaji Efektivitas Manajemen Mutu dalam Pendidikan Anak Usia Dini: (Sebuah Studi Penelitian Lapangan di TK Al Abidin Surakarta): Assessing the Effectiveness of Quality Management in Early Childhood Education: (A Field Research Study at Al Abidin Kindergarten, Surakarta) - Upik Elok Endang Rasmani; Muhammad Ixseas Vridge; Pingky Nur Azizah; Santika Setya Rahmawati (Universitas Ngudi Waluyo, 2024)
This research aims to find out how school quality improvement management is managed by looking at educational input, educational processes and educational output. This research was conducted at TKII Al Abidin Surakarta. The research method used is a qualitative research method with a case study approach. Data collection techniques were carried out through observation and interviews with research subjects or informants, namely school principals. The results found in this research are: (1) TKII Al Abidin's educational input, including human resources, achievement expectations, student focus, and management input; (2) educational processes related to the learning process and performance of teaching staff; (3) educational output that is in line with the objectives of TKII Al Abidin and related to institutional performance. The researcher concluded from the results of research related to the quality management of education in kindergarten that it is good because it is under the auspices of a foundation, so the management of quality management is structured. ABSTRAK Penelitian ini bertujuan untuk mengetahui bagaimana pengelolaan Manajemen Peningkatan Mutu Sekolah dengan melihat input pendidikan, proses pendidikan, dan output pendidikan. Penelitian ini dilakukan di TKII Al Abidin Surakarta. Metode penelitian yang dilakukan adalah metode penelitian kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data dilakukan melalui observasi dan wawancara dengan subjek penelitian atau informan adalah kepala sekolah. Adapun hasil yang ditemukan dalam penelitian ini yaitu: (1) input pendidikan TKII Al Abidin baik sumber daya manusia, harapan prestasi, fokus peserta didik, dan input manajemen; (2) proses pendidikan terkait proses pembelajaran dan kinerja tenaga pendidik; (3) output pendidikan yang sesuai dengan tujuan TKII Al Abidin dan terkait kinerja lembaga. Peneliti menyimpulkan dari hasil penelitian terkait manajemen mutu pendidikan di TK tersebut sudah bagus karena di bawah naungan yayasan, sehingga untuk pengelolaan manajemen mutunya sudah terstruktur.